Bound Ca2+ moves faster and farther from single open channels than free Ca2+ - Mironov, S. L. (Frontiers in Physiology, 2023)
A concept of Ca2+ nanodomains established in the cytoplasm after opening single-calcium channels helps mechanistically understand the physiological mechanisms of Ca2+ signaling. It predicts standing gradients of cytoplasmic free Ca2+ around single channels in the plasma membrane. The fate of bound Ca2+ attracted much less attention. This study aimed to examine the profiles of Ca2+ bound to low-mobility buffers such as bulky Ca2+-binding proteins. The solution of non-linear PDEs for an immobile buffer predicts fast decay of free [Ca2+] from the channel lumen and the traveling wave for bound Ca2+. For low-mobility buffers like calmodulin, the calculated profiles of free and bound Ca2+ are similar. Theoretical predictions are tested by imaging 1D profiles of Ca2+ bound to low-mobility fluo-4-dextran. The traveling waves of bound Ca2+ are observed that develop during the opening of single channels. The findings tempt to propose that Ca2+ signaling may not be solely related by the absolute free [Ca2+] at the sensor location, which is extremely localized, but determined by the time when a wave of bound Ca2+ reaches a threshold needed for sensor activation.